A flexible microwave shield with tunable frequency-transmission and electromagnetic compatibility - Lv, Hualiang (2021)
Wireless techniques have improved life quality for many. However, the drawbacks like instable signal and high loss in air of electromagnetic interference hinder its further development. One solution is to develop a smart material or device, which can selectively receive a specific frequency (fs) of electromagnetic wave with less loss, and simultaneously show effective shielding against unwanted waves (frequency is denoted as fp). A bottleneck has been reached, such that using materials alone is unable to achieve the above due to the limitation of the intrinsic physical properties of materials. Here, a strategy combining the material structure design with a voltage control is proposed to overcome the limitation of materials toward the aforementioned task. The efforts are focused on exploring a suitable electrically tunable material with a sensitive response to an external voltage and the flexibility to be engineered to the needed macrostructure. As a result, the fs region can be fine-tuned to 8–8.4, 8–9.3, and 8–10.3 GHz.